Not Six Times its Angle

Geometry Level 3

We are given sin ( 2 θ ) = 1 3 \sin ( 2 \theta) = \frac 1 3 , and if the value of sin 6 θ + cos 6 θ \sin^6 \theta + \cos^6 \theta is the form of a b \frac a b for coprime positive integers. Find the value of a + b a + b .


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

8 solutions

Mudit Bansal
Jan 27, 2015

another easy solution: sin 6 x + cos 6 x = ( sin 2 x + cos 2 x ) 3 3 sin 2 x cos 2 x ( sin 2 x + cos 2 x ) = 1 3 4 sin 2 2 x × 1 \sin ^{ 6 }{ x } +\cos ^{ 6 }{ x } ={ \left( \sin ^{ 2 }{ x } +\cos ^{ 2 }{ x } \right) }^{ 3 }-3\sin ^{ 2 }{ x } \cos ^{ 2 }{ x } \left( \sin ^{ 2 }{ x } +\cos ^{ 2 }{ x } \right) \\ \quad \quad \quad =1-\frac { 3 }{ 4 } \sin ^{ 2 }{ 2x } \times 1 .On substituting values we get = 1 1 12 = 11 12 =1-\frac { 1 }{ 12 } =\frac { 11 }{ 12 }

very short and simple! Good job Mudit.

Bhupendra Jangir - 6 years, 4 months ago

Noting that a 3 + b 3 = ( a + b ) ( a 2 a b + b 2 ) a^{3} + b^{3} = (a + b)(a^{2} - ab + b^{2}) , sin 2 ( θ ) + cos 2 ( θ ) = 1 \sin^{2}(\theta) + \cos^{2}(\theta) = 1 and

sin ( 2 θ ) = 2 sin ( θ ) cos ( θ ) \sin(2\theta) = 2\sin(\theta)\cos(\theta) we find that

sin 6 ( θ ) + cos 6 ( θ ) = \sin^{6}(\theta) + \cos^{6}(\theta) =

( sin 2 ( θ ) + cos 2 ( θ ) ) ( sin 4 ( θ ) sin 2 ( θ ) cos 2 ( θ ) + cos 4 ( θ ) ) = (\sin^{2}(\theta) + \cos^{2}(\theta))*(\sin^{4}(\theta) - \sin^{2}(\theta)\cos^{2}(\theta) + \cos^{4}(\theta)) =

( s i n 2 ( θ ) + cos 2 ( θ ) ) 2 3 sin 2 ( θ ) cos 2 ( θ ) = (sin^{2}(\theta) + \cos^{2}(\theta))^{2} - 3\sin^{2}(\theta)\cos^{2}(\theta) =

1 3 sin 2 ( 2 θ ) 4 = 1 ( 3 4 ) ( 1 3 ) 2 = 1 1 12 = 11 12 . 1 - 3*\dfrac{\sin^{2}(2\theta)}{4} =1 - (\dfrac{3}{4})(\dfrac{1}{3})^{2} = 1 - \dfrac{1}{12} = \dfrac{11}{12}.

Thus a + b = 11 + 12 = 23 . a + b = 11 + 12 = \boxed{23}.

Chew-Seong Cheong
Jan 27, 2015

sin 2 θ = 1 3 cos 2 θ = 2 2 3 2 cos 2 θ 1 = 2 2 3 \sin{2\theta} = \dfrac {1}{3}\quad \Rightarrow \cos{2\theta} = \dfrac {2\sqrt{2}} {3} \quad \Rightarrow 2\cos^2 {\theta} - 1 = \dfrac {2\sqrt{2}} {3}

cos 2 θ = 1 2 + 2 3 sin 2 θ = 1 2 2 3 \Rightarrow \cos^2 {\theta} = \frac {1}{2} + \frac {\sqrt{2}}{3}\quad \Rightarrow \sin^2 {\theta} = \frac {1}{2} - \frac {\sqrt{2}}{3}

sin 6 θ + cos 2 θ = ( 1 2 2 3 ) 3 + ( 1 2 + 2 3 ) 3 \sin^6 {\theta} + \cos^2 {\theta} = \left( \frac {1}{2} - \frac {\sqrt{2}}{3} \right)^3 + \left( \frac {1}{2} + \frac {\sqrt{2}}{3} \right)^3

= ( 1 8 3 ( 1 4 ) ( 2 3 ) + 3 ( 1 2 ) ( 2 9 ) 2 2 27 ) + ( 1 8 + 3 ( 1 4 ) ( 2 3 ) + 3 ( 1 2 ) ( 2 9 ) + 2 2 27 ) = \left( \frac {1}{8} - 3 (\frac{1}{4})(\frac {\sqrt{2}}{3}) + 3 (\frac{1}{2})(\frac {2}{9}) - \frac {2\sqrt{2}}{27} \right) + \left( \frac {1}{8} + 3 (\frac{1}{4})(\frac {\sqrt{2}}{3}) + 3 (\frac{1}{2})(\frac {2}{9}) + \frac {2\sqrt{2}}{27} \right)

= 2 ( 1 8 + 1 3 ) = 11 12 =2\left( \frac {1}{8} + \frac {1}{3} \right) = \frac {11}{12}

a + b = 23 \Rightarrow a + b = \boxed{23}

Factoring the sum of cubes:

s i n 6 θ + c o s 6 θ = ( s i n 2 θ + c o s 2 θ ) ( s i n 4 θ s i n 2 θ c o s 2 θ + c o s 4 θ ) sin^{6}\theta + cos^{6}\theta = (sin^{2}\theta + cos^{2}\theta)(sin^{4}\theta - sin^{2}\theta *cos^{2}\theta + cos^{4}\theta)

= s i n 4 θ s i n 2 θ c o s 2 θ + c o s 4 θ = sin^{4}\theta - sin^{2}\theta *cos^{2}\theta + cos^{4}\theta

= ( c o s 2 θ s i n 2 θ ) 2 + s i n 2 θ c o s 2 θ = (cos^{2} \theta - sin^{2} \theta)^2 + sin^{2}\theta * cos^{2} \theta

= ( c o s 2 2 θ ) + 1 4 s i n 2 2 θ = (cos^{2} 2\theta) + \frac{1}{4}sin^{2} 2\theta

= ( 1 s i n 2 2 θ ) + 1 4 s i n 2 2 θ = (1 - sin^{2} 2\theta) + \frac{1}{4}sin^{2} 2\theta

= ( 1 1 9 ) + 1 36 = (1 - \frac{1}{9}) + \frac{1}{36}

= 8 9 + 1 36 = \frac{8}{9} + \frac{1}{36}

= 32 + 1 36 = \frac{32 + 1}{36}

= 33 36 = 11 12 = \frac{33}{36} = \frac{11}{12}

Thus, a = 11 a = 11 , b = 12 b = 12 , a + b = 23 a + b = 23

Imam Edogawa
Jun 3, 2015

Same with mudit

Curtis Clement
Feb 16, 2015

( s i n 2 θ + c o s 2 θ ) 3 = s i n 6 θ + c o s 6 θ + 3 ( s i n 2 θ c o s 2 θ ) ( s i n 2 θ + c o s 2 θ ) (sin^2 \theta + cos^2 \theta )^3 = sin^6 \theta + cos^6 \theta + 3(sin^2 \theta cos^2\theta)(sin^2 \theta+ cos^2 \theta) Using sin2 θ \theta = 2sin θ \theta cos θ \theta sin 6 θ + c o s 6 θ = 1 3 4 s i n 2 2 θ = 1 1 12 = 11 12 \Rightarrow\sin^6 \theta + cos^6 \theta = 1 - \frac{3}{4}sin^{2} 2\theta = 1 - \frac{1}{12} = \boxed{\frac{11}{12}}

Sagnik Ghosh
Feb 1, 2015

s i n 2 θ = 2. s i n θ . c o s θ = 1 3 . . . . . . . . . ( 1 ) s i n 2 θ + c o s 2 θ = 1 . . . . . . . . . . . . . . . . ( 2 ) s i n 6 θ + c o s 6 θ ( s i n 2 θ + c o s 2 θ ) 3 3 s i n 2 θ c o s 2 θ ( s i n 2 θ + c o s 2 θ ) P u t t i n g t h e v a l u e s f r o m ( 1 ) a n d ( 2 ) 1 3 3. { 1 6 } 2 . ( 1 ) 1 1 12 11 12 L e t 11 12 b e r e p r e s e n t e d a s a b F i n a l l y , T h e a n s w e r w i l l b e a + b i . e . 23 sin\quad 2\theta \quad =\quad 2.sin\theta .cos\theta \quad =\quad \frac { 1 }{ 3 } .........(1)\\ sin^{ 2 }\theta \quad +\quad cos^{ 2 }\theta \quad =\quad 1\quad ................(2)\\ \\ sin^{ 6 }\theta \quad +\quad cos^{ 6 }\theta \quad \\ \Rightarrow \quad (sin^{ 2 }\theta +cos^{ 2 }\theta )^{ 3 }\quad -\quad 3\quad sin^{ 2 }\theta cos^{ 2 }\theta \quad (sin^{ 2 }\theta +cos^{ 2 }\theta )\\ \\ Putting\quad the\quad values\quad from\quad (1)\quad and\quad (2)\\ \Rightarrow \quad { 1 }^{ 3 }\quad -\quad 3.{ \left\{ \frac { 1 }{ 6 } \right\} }^{ 2 }.(1)\\ \Rightarrow 1\quad -\quad \frac { 1 }{ 12 } \\ \Rightarrow \frac { 11 }{ 12 } \\ Let\quad \frac { 11 }{ 12 } \quad be\quad represented\quad as\quad \frac { a }{ b } \\ \\ Finally\quad ,\quad The\quad answer\quad will\quad be\quad \boxed { a+b } \quad i.e.\quad \boxed { 23 }

Aditya Purohit
Jan 26, 2015

sin2A= 2sinAcosA

→ sinAcosA= 1/6

Also sin^6A + cos^6A = (sin^2A + cos^2A)^3 - 3sin^2Acos^2 A( sin^2A + cos^2A)

substitute value of sinAcosA nget d ans.

why are you leaving the proof in half complete it dont make it as a mystery

sudoku subbu - 6 years, 4 months ago

Log in to reply

sin^6A+ cos^6 A=1-3sin^2A cos^2A =\frac{1}{4}[4-3(2sin^2A cos^2A)^2] = 1-3(\frac{1}{3})^2 ÷4 = 1-(\frac{1}{12}) =11÷12

Prince Patel - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...